Comparison of lameness outcomes in horses with acute or chronic digital lameness that underwent magnetic resonance imaging. Issue 5 (2nd September 2020) - Koch, DW; Barrett, MF; Jackman, BR; MacDonald, D; Goodrich, LR
ABSTRACT: Aims: To compare the outcome, in terms of lameness score or return to athletic function, of horses with acute vs. chronic digital lameness that underwent magnetic resonance imaging (MRI) of the distal limb and to compare the proportion of horses that received intra-articular therapy of the distal interphalangeal (DIP) joint and pattern of diagnostic analgesia in these groups. Methods: This is a retrospective study of horses (n = 95) with acute (≤12 weeks; n = 46) or chronic (>12 weeks; n = 49) digital lameness that underwent MRI of the distal limb from 2009–2016, at two equine referral centres in the USA. Criteria for inclusion in the study were that a majority of lameness localised distal to the fetlock, and that lameness assessments for ≥12 months following MRI could be obtained from the medical record or the owner could be interviewed regarding their horse's athletic function. Outcome was characterised by an improvement score where 2 = return to work at a previous or higher level or lameness improved by one grade or more, 1 = return to work at a lower level or lameness improved by less than one grade, and 0 = did not return to work or lameness grade worsened. Whether horses had received intra-articular therapy of the DIP joint and the pattern of diagnostic analgesia prior to MRI was also obtained from medical records or by interviewing the owner. Results: There was a difference (p = 0.004) in the proportion of horses assigned to improvement scores of 0, 1 and 2 between horses with acute or chronic lameness. There was no evidence of a difference in the likelihood of having received intra-articular therapy of the DIP joint prior to MRI between horses with chronic or acute lameness (p = 0.085). Similarly, there was no evidence of a difference in the pattern of diagnostic analgesia prior to MRI between the two groups (p = 0.94). Eighty-two percent of owners of horses with acute and 62% of those with horses with chronic lameness had a positive opinion of the utility of MRI as a diagnostic modality. Conclusion: In a population of horses with digital lameness undergoing MRI, a difference in the outcome, in terms of lameness score or return to athletic function was identified between horses with acute lameness compared to those with chronic lameness. Clinical relevance: Horses with digital lameness that undergo MRI when the lameness is acute may have an improved prognosis due to accurate diagnosis and earlier application of appropriate therapy.